Follow-Up of Patients Undergoing Thalidomide Therapy for Transfusion-Dependent β-Thalassemia: A Single Thalassemia Center Cohort Study - Kiran Kanwal; Asma Akbar; Shakeel Ahmad Leghari; Irum Jabeen; Sonia Ilyas; Asmat Ullah; Zuhaib Hassan; Sajawal Shareef (Pakistan Journal of Medicine and Dentistry)
Background: Thalassemia is a common inherited disorder globally. This study aimed to evaluate the long-term effects of thalidomide therapy in patients with transfusion-dependent β-Thalassemia (TDT).